En rekonstruksjon av variasjoner i breutbredelse gjennom holosen på Svartfjelljøkelen, Bergsfjordhalvøya. En studie basert på proglasiale innsjøsedimenter og kvartærgeologisk kartlegging - Eeg, Thea Thingelstad (The University of Bergen, 2012)
Svartfjelljøkelen is a small (5 km2), maritime ice cap situated on a mountain plateau on the Bergsfjord peninsula in Finnmark, Northern Norway, with an average equilibrium line altitude (ELA) close to 870 m altitude. Several prominent moraines are deposited between the present day glacier snout and the downstream lake Bergsfjordvatnet. Photographs show that the glacier has receded substantially during the last 100 years or so. In an effort to reconstruct continuous glacier activity throughout the Holocene (<11 700 year), two piston cores and HTH- cores were retrieved from the downstream lake, which annually receives sediment laden melt water originating from the glacier, for further analysis. The lake was mapped using ground penetrating radar (GPR) prior to coring in order to secure that analysis were carried out on cores that are representative of the general influx of sediments. The lake sediments were analysed by investigating geochemical elements (XRF), rock magnetic properties, dry bulk density (DBD), weight loss-on-ignition (LOI) and grain size distribution. The resolution of the various methods range from 5 cm to 0,005 cm. Sediment samples were collected from the surrounding catchment in order to cross-validate the glacier signal, as observed in the lake. The relationship between MS and titanium proved, together with the MS versus manganese/titanium, to be particular good indicators of glacial and extra-glacial sediment sources. 210Pb dating of the uppermost sediments and 14C dating of macrofossils throughout the piston cores provided a robust age- depth relationship that covers the last 9000 years. Quaternary geological mapping of the area revealed the impact of glaciofluvial, fluvial and colluvial processes. Marginal moraines were indirectly dated using historical records, which again were connected to certain levels in the lake sediments. This was feasible due to successful 210Pb dating of the lake sediments. By tying the age of the moraines to the independently dated lake sediments, a regression ...